Changes in the production of energy from renewable sources in the countries of Central and Eastern Europe - Rokicki, Tomasz; Koszela, Grzegorz; Ochnio, Luiza; Perkowska, Aleksandra; Bórawski, Piotr; Bełdycka-Bórawska, Aneta; Gradziuk, Barbara; Gradziuk, Piotr; Siedlecka, Agnieszka; Szeberényi, András; Dzikuć, Maciej (Frontiers in Energy Research, 2022)
The main aim of this paper was to determine changes in the production of renewable energy in the countries of Central and Eastern Europe. The specific objectives were to determine the degree of concentration of renewable energy and the pace of changes in the volume of production of this energy from individual sources in the countries of Central and Eastern Europe, as well as to determine the structure according to renewable energy sources, to show the directions of changes. Countries of Central and Eastern Europe were covered for the research, which means a total of 23 countries included. The data used in the study obtained from the IRENA and World Bank databases. The research period covered the years from 2011 to 2019. For data analysis the following methods were used: Index method, Gini coefficient, Lorenz curve and Gradation Data Analysis. In the case of pace of changes and the structure of renewable energy produced, difference can be found between the EU member countries of Central and Eastern Europe and the group of countries outside the EU. The fastest growth in energy production from renewable sources was achieved in EU member countries of Central and Eastern Europe. In the EU member countries of Central and Eastern Europe, the production of solar energy, wind energy, and bioenergy were developed. In other countries, the production of hydropower was developed, which was treated as a traditional source of energy. Generally, in countries of Central and Eastern Europe, the development of energy based on renewable energy sources was not dependent on the pace of economic development of the country.